Dimensions of sports and recreational service quality influencing member satisfaction at Ara Muay Thai gym / Nellisa Nursyafira Mohd Fadzli, Fatin Nur Farisha Mohd Razali and Nor Norita Japri - Mohd Fadzli, Nellisa Nursyafira; Mohd Razali, Fatin Nur Farisha; Japri, Nor Norita (2020)
The fitness industry is growing at a progressive pace with an increasing number of gym memberships as well as fitness centres. This has led to intense competition. This situation also has made it difficult to entice new members and encourage them to participate in workout programmes. Focusing on delivering excellent service quality at the gym can heighten member satisfaction with the service. The purpose of this paper is to apply the Scale of Service Quality in Recreational Sports (SSQRS) dimensions to deliver member satisfaction at Ara Muay Thai Gym. The SSQRS dimensions encompasses physical environment quality, interaction quality, outcome quality, and programme quality. Data were analysed from 113 questionnaires received from registered members of Ara Muay Thai Gym located in Petaling Jaya, Selangor. Results of the regression analysis revealed that SSQRS dimensions played a major role towards member satisfaction and suggested that physical environment quality, interaction quality and outcome quality significantly affect member satisfaction. In the context of a gym, the results concluded that these three dimensions of sports and recreational service quality will lead to satisfaction of members at Ara Muay Thai Gym, which the company should leverage on for future growth. It is recommended that Ara Muay Thai Gym offer personalized workout programmers to fit individual members ability levels and fitness goals, to optimize space by filling it with value-added services, and to offer workout streaming services for members. These strategies aimed to improve members’ satisfaction which subsequently increase revenue growth.